Mechanisms for Administrating Tasks and Editing Data Bases in Hybrid email/SMS Info-Communicational Systems - Andranik E. Mkhitaryan (Изд-во НАН РА)
Info-communicational system ‘Mail2SMS’ [1] is a flexible mechanism to notify the receivers of email about the delivered e-mail by SMS messages. In such systems every user should be able to control the list of allowed/disallowed notifiers. In this article a possible solution to this problem is considered by special commands.
Keywords: Mathematics; Computer software